High precision assembly and efficient dispensing approaches for millimeter objects. (19th June 2019) - Li, Ying; Zhang, Dapeng; Xu, De
In this article, high precision alignment and efficient dispensing approaches for millimeter objects are proposed. Firstly, a thin component and a cylindrical component are assembled together based on microscopic vision and laser range sensor. If the normal vector of upper surface of thin component is not perpendicular to the optical axis of side camera, the region around the lower edge line will be blurred easily in image. In order to measure the orientation of the thin component with high precision, a novel method based on laser range sensor is proposed. The two components are assembled after orientation and position alignment. In order to bond the two components, the glue is dispensed into all the 16 holes on the components. For keeping the two components firm after being dispensed, the volume of glue dispensed into the 16 holes should be controlled precisely. A laser range sensor is employed to measure the volume of fluid glue. The dispensing process should be finished in a limited time for the characteristics of fluid glue that will change with time. The fluid glue should be dispensed into the hole for some times to reach the expected volume. However, it is necessary to wait a little time in order to obtain stable level of glue after the glue is dispensed into the hole. Therefore, a dual dispensing strategy with higher efficiency is developed which fully utilizes the waiting time. Experimental results validate the effectiveness of the proposed system and methods.